Collection, analysis and on-line experimentation of ocean color remote sensing data An appraisal off the Southwestern Iberian Peninsula - D'Alimonte, Davide (2019)
This document concerns the collection, analysis and on-line experimentation of ocean color data off the Western Iberian Peninsula. Field measurements have been acquired during the BIOMETORE field campaign in summer 2016 to evaluate and enhance Earth observation capabilities of the Copernicus program. Deliverables of the Ocean and Land Colour Instrument on board of the Sentinel-3 satellite of the European Space Agency are of specific interest. Preliminary evaluations confirm the quality of the in situ measurements to address the match-up future analysis of radiometric values and derived data products. On-line experimentation undertaken with the WebEnhanced Service To Ocean Color demonstrates the feasibility of enabling in a transparent way the user's access to complex functionalities such as neural network applications.